IMPLEMENTASI KEBIJAKAN PENGATURAN PASAR TRADISIONAL DI KOTA SEMARANG - Pramana, Hafiz Gilang Setia; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Market Utilization Policy in Semarang City which has formulated in local Regulation of Semarang City Number 9 of 2013 concerning traditional market arrangement is an effort of Semarang City Government to create tidy, safe, clean and healthy traditional market; intensify services to the community and make the traditional market as main revenue to the local economy. Aside from being the capital city in the province of Central Java, Semarang City is also the center of trading among small towns around it, such as Demak, Kendal, Kudus, Pati and others. So the city must manage the traditional market maximally. therefore The focus of this research is about the implementation of market utilization policy in Semarang City. This research purposes are describing the implementation of market utilization policy and also to know the determinant factors of successful implementation of market utilization policy in Semarang City. This research is descriptive qualitative research. Data collection is done by observation, documentation studies and in-depth interviews from informants who is involved in the implementation policy of market utilization in Semarang city. The result of this research is that the implementation of market utilization policy in Semarang City is not maximized, it is caused by several factors that obstruct the implementation policy, such as the existence of market traders who do not obey the regulation policy, limited budget and minimum number of agents compared with the masive market trader. Based on the reserach result, the researchers suggested that there must an inhancement in optimizing the determinants factors of the implementation of market utilization policy in the city of Semarang which still considered deficient. Suggestions given by researchers are expected to assist the government in the implementaton policy. So that the implementation of market utilization policy in Semarang City can run more effectively and efficiently. Keywords: